Problematica sărăciei în România în perioada 1990−2020 - Mihăilescu, Adina (Calitatea Vieții, 2021)
The entire world, including the countries of the European Union, has been facing economic and financial difficulties for several years, which has somewhat affected the countries where people's lives are compared with the concept under our debate, that of welfare. The scientific approach of this study is to compare the most important and used types of salary income in the purchase of various food, non-food and service products on the market. The paper highlights the importance of the consumption model for the realistic measure of the phenomenon of poverty in a country or in a certain period of time, and of course, the measures/policies that can be taken/applied to reduce poverty, support vulnerable groups, and estimate the required costs, the satisfaction of urgent needs.